Cross-presentation of exogenous antigens on MHC I molecules. - Colbert, Jeff D. (Curr Opin Immunol, 2020)
For recognition by CD8 T cells, most cells present peptides from endogenously expressed self or foreign proteins on MHC class I molecules. However, specialized antigen presenting cells, such as DCs and macrophages, can present exogenous antigen on MHC-I in a process called cross-presentation. This pathway plays key roles in antimicrobial and antitumor immunity, and also immune tolerance. Recent advances have broadened our understanding of the underlying mechanisms of cross-presentation. Here we review some of these recent advances, including the distinct pathways that result in the cross-priming of CD8 T cells and the source of the class I molecules presenting exogenous peptides.